Rumination and coping: How emerging adults deal with romantic breakups - Adikusumah, R. Muhammad Rafsanzani; Kustimah; Meindy, Nadhira (Universitas Mercu Buana Yogyakarta, 2023)
Romantic relationship breakups among emerging adults are often described as unpleasant, painful, or stressful. During these stressful periods, emerging adults may engage in rumination that could prolong the stress, while also engaging in different strategies to cope with their condition. This study aims to determine the relationship between rumination and coping strategies used by emerging adults in dealing with breakups in romantic relationships. As many as 141 participants were recruited by using convenience sampling for this study. The measuring tools used are the Ruminative Response Scale RRS-10) and the Brief COPE which has been adapted to Bahasa Indonesia. The results showed that there was a significant positive relationship between rumination and problem-focused coping strategies and there was a positive relationship between rumination and dysfunctional coping strategies. It is also found that different types of rumination are correlated with different coping strategies in emerging adults who have gone through romantic breakups. This study has practical implications for the development of interventions to overcome relationship breakups. Keyword: Rumination; coping stress; emerging adulthood; romantic breakup; relationship dissolution